2018
DOI: 10.1186/s40902-018-0171-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of changes in airway space after bimaxillary orthognathic surgery with maxillomandibular setback and their association with obstructive sleep apnea

Abstract: BackgroundBimaxillary orthognathic surgery with maxillomandibular setback is often accompanied by changes in airway space. We analyzed the changes in airway space before and after surgery and assessed their association with obstructive sleep apnea.MethodsThis study is based on the cohort of 13 adult patients (9 males, 4 females, average age 23.85 years) who underwent bimaxillary orthognathic surgery with maxillomandibular setback.We performed computed tomography and portable polysomnography before and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…Obstructive sleep apnea (OSA) refers to sleep-disordered breathing showing repetitive episodes of upper airway collapse during sleep [1]. The risk factors for OSA have been reported as old age, male, smoker, alcohol use, obesity, and craniofacial abnormality [26]. Therefore, the pathogenesis of OSA may be related to altered anatomy (small box) and physiology (increased collapsibility) of the upper airway.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) refers to sleep-disordered breathing showing repetitive episodes of upper airway collapse during sleep [1]. The risk factors for OSA have been reported as old age, male, smoker, alcohol use, obesity, and craniofacial abnormality [26]. Therefore, the pathogenesis of OSA may be related to altered anatomy (small box) and physiology (increased collapsibility) of the upper airway.…”
Section: Introductionmentioning
confidence: 99%
“…When mandibular setback was performed with maxillary advancement or posterior impaction, the pharyngeal airway volume significantly decreased. However, it did not significantly affect AHI values or induce OSA [6].…”
Section: Introductionmentioning
confidence: 71%
“…The TPV was decreased to 82.0~96.8% in the short term after surgery and recovered to 84.5~98.0% around 6 months after surgery (Table 2). However, the degree of airway reduction was smaller than that in mandibular setback surgery alone [6,14,16,25,26]. Immediately after surgery, airway narrowing was more severe because of soft tissue edema.…”
Section: Significant Airway Reduction After Mandibular Setback Surgerymentioning
confidence: 88%
See 1 more Smart Citation
“…A three-dimensional (3D) PAS volume showed a significant decrease in the oropharyngeal airway, and no significant change has been observed in the sleep symptoms [8]. Reports indicated that bimaxillary orthognathic surgery to reduce PAS played a role, but it does not increase AHI, one of the important determinants of sleep apnea [18,19,21,23]. As a result of a significant decrease in the airway space, it did not influence the AHI-values or cause OSA.…”
Section: Discussionmentioning
confidence: 98%